1989
DOI: 10.1093/geronj/44.4.p114
|View full text |Cite
|
Sign up to set email alerts
|

A New Scale for the Assessment of Functional Status in Alzheimer's Disease and Related Disorders

Abstract: Assessment of the functional competencies of patients with dementia is typically conducted in an indirect manner. Psychological tests of cognition or descriptions by relatives or other caregivers are often used to make judgments as to the patient's ability to adapt to the demands of the environment. However, these methods have built-in biases. The need for direct assessment of functional status was addressed by developing a standardized operational procedure to examine areas of functional competence which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
215
2
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(238 citation statements)
references
References 0 publications
5
215
2
9
Order By: Relevance
“…Given the dearth of measures of everyday functioning available for use in minority and non-English speaking populations, the IQCODE appears to have significant cross-cultural applications. There are some limitations to this and other functional measures which rely solely on information obtained from an informant rather than performance-based measures of everyday behaviors (e.g., Direct Assessment of Functional Status, Loewenstein et al, 1989). However, it also has many advantages over such performance-based measures including ease and brevity of administration, as well as cost efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Given the dearth of measures of everyday functioning available for use in minority and non-English speaking populations, the IQCODE appears to have significant cross-cultural applications. There are some limitations to this and other functional measures which rely solely on information obtained from an informant rather than performance-based measures of everyday behaviors (e.g., Direct Assessment of Functional Status, Loewenstein et al, 1989). However, it also has many advantages over such performance-based measures including ease and brevity of administration, as well as cost efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive constructs that overlap with judgment include everyday problem solving, everyday decision making, social problem solving, and practical intelligence (Marsiske & Margrett, 2006;Thornton & Dumke, 2005;Willis, 1996), and objective measures of these constructs include the following: Predicaments Task (Channon & Crawford, 1999), Reflective Judgment Dilemmas (Kajanne, 2003), Practical Problems Test (Denney & Pearce, 1989); Everyday Cognition Battery (Allaire & Marsiske, 1999); Everyday Problems Test (Willis & Marsiske, 1993), Everyday Problem Solving Inventory (Cornelius & Caspi, 1987), Everyday Problems Test for Cognitively Challenged Elderly (EPCCE; Willis, 1993;Willis et al, 1998), and the Direct Assessment of Functional Status (Lowenstein et al, 1989). Instruments also have been developed to assess competence to consent to medical treatment and/or research (see Fitten, Lusky, & Hamann, 1990;Grisso, Appelbaum, & HillFotouhi, 1997;Marson, Hawkins, McInturff, & Harrell, 1997;Marson, Schmitt, Ingram, & Harrell, 1994;Vellinga, Smit, van Leeuwen, van Tilburg, & Jonker, 2004).…”
mentioning
confidence: 99%
“…Loewenstein and colleagues (4) reported that the Direct Assessment of Functional Status Scale significantly discriminated clinic patients with Alzheimer's disease from normal elderly subjects and from a group of elderly outpatients with major depression. To our knowledge, the measure has not been tested in a group of older patients with schizophrenia.…”
mentioning
confidence: 99%